PERLINDUNGAN TERHADAP ANAK PELAKU TINDAK PIDANA DALAM PERSPEKTIF UNDANG-UNDANG SISTEM PERADILAN PIDANA ANAK - Dahlia, Roza (Ensiklopedia Sosial Review, 2019)
Article 1 number 2 of the Child Protection Act states that Child Protection is all activities to guarantee and protect children and their rights so that they can live, grow, develop and participate optimally in accordance with human dignity and dignity, and receive protection from violence and discrimination. This research will look at the extent to which the protection of child perpetrators of crime is in the perspective of the criminal justice system for children. The method used is a normative juridical research method. A child who is involved in a criminal offense must be held responsible and if the child is proven guilty may be subject to criminal sanctions for the deeds he has committed. Article 3 and Article 4 of the Law on the juvenile justice system already includes all the children's rights from the investigation stage to the guidance stage after serving the crime. The efforts made to protect children are given in the form of rights contained in this law contained in.